Penguatan Peran UMKM melalui Pendampingan Pembuatan Laporan Keuangan - Rhosalina Damayanti; Adrian Izaak Rompis (Universitas Kristen Satya Wacana Salatiga, 2021)
UMKM are expected to be able to support economic growth in Indonesia. This expectation must be answered by providing financial reports. This community service carried out at Waroeng Pitoe, that was not yet fully capable of recording financial accounting and reporting. The purpose of this community service is a form of active participation by academics to increase Waroeng Pitoe's understanding of the importance of financial reports and to produce financial reports. This community service is useful for helping in providing financial reports as a means of assessing financial performance and helping business decision making. Community service was carried out by assisting in the preparation of financial report templates, counseling and training. The result of this community service was to increase the understanding of the directors and employees of Waroeng Pitoe regarding the importance of the availability of financial reports, assisting the process of accounting records, and preparing simple financial reports.